The antitumor activity of thymoquinone and thymohydroquinone in vitro and in vivo - Ivankovic, S.; Stojkovic, R.; Jukic, M.; Milos, M. (Experimental Oncology, 2006)
Aim: The aim of the study was to investigate antitumor activity of thymoquinone (TQ) and thymohydroquinone (THQ) in vitro and in vivo. Materials and Methods: In the in vitro experiments, L929 mouse ?broblasts and two tumor cell lines (squamous cell carcinoma (SCC VII) and fibrosarcoma (FsaR)) were used. The cells were cultured with 0.1 or 0.01 mg/ml TQ or THQ for 24 h, and cytotoxicity assay was performed with the use of crystal violet staining technique. For in vivo antitumor efficiency evaluation of new compounds two murine tumor models (fibrosarcoma (FsaR) and squamous cell carcinoma (SCC VII)) were used. The used dose was equal for both substances. Antitumor effect of 4 intratumoral injections of TQ and THQ at the dose of 5 mg/kg was evaluated by comparison of tumor growth kinetics between treated and control animals. Results: In vitro study showed that TQ and THQ exhibit statistically significant cytotoxic activity (p < 0.01). The cytotoxic activity was dose dependent and more expressed against tumor cells than against L929 fibroblasts. The result of antitumor activities of TQ and THQ in vivo reached TGI = 52% and it was statistically significant (p < 0.05). Conclusion: The results indicate that THQ antitumor activity may be improved with further dose increase of the investigated substance. Цель: исследовать противоопухолевую активность тимохинона (TХ) и тимогидрохинона (TГХ) in vitro и in vivo. Материалы
и методы: в экспериментах in vitro использовали линию клеток фибробластов мыши L929 и две линии опухолевых клеток
мыши (плоскоклеточной карциномы SCC VII и фибросаркомы FsaR). По достижении монослоя, клетки инкубировали с 0,1
или 0,01 мг/мл TХ или TГХ, после чего цитотоксический эффект определяли по включению кристаллического фиолетового.
Противоопухолевый эффект 4-кратного внутриопухолевого введения TХ или TГХ в дозе 5 мг/кг in vivo в экспериментальных
моделях FsaR и SCC VII определяли по кинетике опухолевого роста. Результаты: исследования in vitro показали, что TХ
и TГХ обладают статистически значимой цитотоксической активностью (p < 0,01), причем таковая носит дозозависимый
характер и в большей степени проявляется по отношению к линиям опухолевых клеток, чем фибробластов. Противоопухолевый
эффект соединений статистически достоверный, ингибирование опухолевого роста достигало 52% (p < 0,05).
Выводы: противоопухолевая активность ТГХ может быть повышена путем дальнейшего повышения дозы вещества.